The effect of age on sprinting performance during acceleration in long jump athletes - Mironov, A. O.; Gerasimov, M. V.; Vinogradova, O. P.; Spiridonov, E. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to study the peculiarities of the influence of the age factor on the manifestation of speed and strength qualities in the run-up phase of long jumpers.